ANALISIS DISKRESI KEPOLISIAN DALAM PENYIDIKAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (Studi Pada Unit PPA Sat Reskrim Polresta Padang) - Rido Matua Simamora (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
One of the objectives of the enactment of Law Number 23 Year 2004 on the Elimination ofDomestic Violence (PKDRT) is to maintain the integrity of harmonious and prosperoushouseholds. The police have the authority to enforce the law and ensure the security andorder of the people. The task can not be done only to rely on the legislation, therefore thepolice are given the authority to do the discretion of the police. In the writing of this thesisthe author discusses about the analysis of police discretion conducted by policeinvestigators in Polresta Padang in order to investigate the crime of violence in thehousehold . Related to this the type of research specification used is descriptive analytical.Based on the result of research that discretion act by the investigator in the settlement ofCriminal Act of Domestic Violence in Padang Polresta law area consist of: mediationeffort which initiated and done by Polri, termination of case and case waiver of case ofkekerasn in that household. There are two factors that can drive the discretion action are:internal factors and external factors. This internal factor is based on the legal basisapplicable to the exercise of discretionary authority by the police as well as the ordersfrom superiors to settle criminal cases which can be resolved through the ADR mechanismand for external factors namely the support of the community, and the goodwill of the thelitigant to solve his case in the best possible way. The obstacles faced in theimplementation of police discretion in the investigation of Domestic Violence Crime byPPA Unit Sat Reskrim Poresta Padang is the absence of a rule of law that specifically andfirmly regulate the police discretion itself applicable in the legal system in Indonesia atthis time, so that in the existing rules currently requires investigators to follow up onincoming cases. In other words investigators are required to process all incoming cases inaccordance with applicable legal procedures.